2016
DOI: 10.4149/gpb_2016018
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic properties and arterial structure in male rat offspring with fetal hypothyroidism

Abstract: Abstract. Thyroid hormones (THs) play a crucial role in the development of different systems during fetal life; fetal hypothyroidism (FH) is associated with reduced cardiac function and dimensions in neonates. The aim of this study is to determine whether TH deficiency during fetal life is associated with arterial structural and hemodynamic changes during adulthood. Hypothyroidism was induced by adding 0.025% 6-propyl-2-thiouracil in drinking water throughout pregnancy, while controls consumed only tap water. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…9,10 Of note, already at the age of 6 weeks, the progeny of PTU-treated dams demonstrated restored blood levels of thyroid hormones and TSH, 20 which is consistent with other studies, where the restoration of thyroid state was observed in 4 weeks after PTU withdrawal. 8 Based on the above, we can consider that the adult rats from PTU group had an euthyroid status for at least 4 weeks before their arteries were taken for in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Of note, already at the age of 6 weeks, the progeny of PTU-treated dams demonstrated restored blood levels of thyroid hormones and TSH, 20 which is consistent with other studies, where the restoration of thyroid state was observed in 4 weeks after PTU withdrawal. 8 Based on the above, we can consider that the adult rats from PTU group had an euthyroid status for at least 4 weeks before their arteries were taken for in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…7 On the other hand, high blood pressure does not always develop in adult progeny of hypothyroid rats. 8,9 The diversity of results suggests that there are adverse circulatory alterations only in certain organs, which might be more susceptible to the developmental thyroid deficiency than others. For example, antenatal/early postnatal hypothyroidism causes increased contractility of coronary vasculature in adult rats, despite the absence of evident alterations in their thyroid function and blood pressure level.…”
Section: Introductionmentioning
confidence: 99%
“…Ghanbari et al have shown that offspring rats with TCH had lower serum TT 4 and TT 3 until days 14 and 21 after birth, respectively, despite their thyroid hormone levels being comparable to normal rats 90 days after birth [59]. Mooradian et al have reported that thyroid hormones have different effects on GLUTs expression during development and in adulthood [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that adult hypothyroidism had no effect on GLUT2 and GcK expression in both islets and liver [70, 71]. In this study, we used a transient model of CH, where thyroid hormone levels were similar to normal rats, whereas adult hypothyroid rats usually have lower than normal levels of thyroid hormones [59]. …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in many mammalian species the blood concentration of thyroid hormones was shown to be higher during the early stages of development compared to adulthood. For example, a rise in blood triiodothyronine (T 3 ) concentration was shown between gestational week 30 and birth in humans and between birth and the 3rd postnatal week in rats [49,50]. Thyroid hormones can have rapid and long-term effects on eNOS expression and/or activity in endothelial cells (Figure 1).…”
Section: Thyroid Hormones and Nomentioning
confidence: 99%